2017
DOI: 10.1038/cr.2017.58
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9-mediated genome editing in one blastomere of two-cell embryos reveals a novel Tet3 function in regulating neocortical development

Abstract: Studying the early function of essential genes is an important and challenging problem in developmental biology. Here, we established a method for rapidly inducing CRISPR-Cas9-mediated mutations in one blastomere of two-cell stage embryos, termed 2-cell embryo-CRISPR-Cas9 injection (2CC), to study the in vivo function of essential (or unknown) genes in founder chimeric mice. By injecting both Cre mRNA and CRISPR-Cas9 targeting the gene of interest into fluorescent reporter mice, the 2CC method can trace both w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…This is in line with our observation that Tet3 KD NPCs form clusters of cells that resemble ES-colonies and are OCT4-positive. Additionally, TET3 has been implicated in regulation of synaptic transmission [60,61] and fear-extinction memory [21], which suggests a pivotal role in the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with our observation that Tet3 KD NPCs form clusters of cells that resemble ES-colonies and are OCT4-positive. Additionally, TET3 has been implicated in regulation of synaptic transmission [60,61] and fear-extinction memory [21], which suggests a pivotal role in the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…This ensures that organs will comprise cells of mixed progeny (wild type or mutant) derived from either of the two initial cells. The latter approach proved successful in a recent report where Tet3 functions were illustrated in the mosaic mutant (Wang et al, 2017). Although this is still an on-going study, we can obtain Atoh1 −/− mosaic mice that survive until at least postnatal day 7 (P7).…”
Section: Discussionmentioning
confidence: 95%
“…Fortunately, the F0-7 male rabbits could live to sexual maturity and were used for mating with the WT rabbits. The mosaicism in the F0-7 rabbits indicated that germline and genotype chimeras generated by CRISPR/Cas9 could significantly expand studies of unknown gene functions in cells or animals ( Wang et al, 2017 ). We could not obtain homozygous gene knockout rabbits owing to the high mortality rate of the FBN1 Het rabbits.…”
Section: Discussionmentioning
confidence: 99%